Roof support design of an underground coal mine - Sharma S.K.; Jaiswal A.; Shrivastva B.K. (My University, 2025)
This paper deals with roof-bolt support pattern design. It contains both the conventional approach, based on RMR, and numerical approach, based on three-dimensional finite-element-method for support design. Varying parameters which are likely to influence the roof stability such as gallery width, thickness of the coal in the roof and bolt pattern were considered in the modelling of this system. Horizontal induced tensile stress was considered within this analysis. The results of the existing case were taken as a foundation to work from and compared with other models.